“Cruzando a linha”: afro-religiosidade, implementação da lei 10.639/03 e as fronteiras da educação escolar-um estudo com professores da educação básica - OLIVEIRA, Ilka Joseane Pinheiro (Universidade Federal do Pará, 2019)
This dissertation constitutes a reflection about the role of Afro-religiosity in education as a theme capable of rethinking the notion of subject, education and culture in the institutional spaces of teaching, promoting the debate of ethnic-racial differences aimed at teachers of basic education, Having as subjects of this research students of the Specialization Group "Policies of Racial Equality in the School - III Class of the African and Afro-Brazilian Knowledge in the Amazon: implementation of Law 10.639/03", promoted by the Federal University of Pará - UFPA, from Of the Group of Afro- Amazonian Studies - GEAAM in partnership between Group of Studies Society, Culture and Education - GESCED, from 2015 to 2016. The locus of the research occurred in the pole of Castanhal. The research developed from a theoretical perspective of cultural studies with categories that debate culture, identity and power, which helped to think the religious field, and more specifically the plots and meanings produced by the teachers about Afro-Brazilian religions from this specialization. The research is inserted in a postcritical perspective in education and is qualitative. As a methodological strategy, participant observation was based on ethnography, based on analysis of oral and written narratives. Among the oral ones, the analysis was based on semi-structured interviews of teachers and narratives recorded in academic programs with the participation of the black, Afro-religious movement and members of the coordination of the postgraduate course. From the written sources we use reports from the subject "Afro-Brazilian culture and religions" and from the final works produced by the teachers. The first findings are that education and Afro-religiosity think of it as a hybrid frontier of difference in school, which has specific historical-social constructions, of the places accepted from where blacks and Afro-religious should occupy. Afro-religiosity is not included as a specific and separate point in the text of the National Curriculum Guidelines for Ethnic-Racial Relations Education or Law 10.639 / 03 that should be taught in schools. But in a movement of cultural processes where symbols are appropriated in various ways, they take shape over the teachers' pedagogical experiences that are marked and remarked by Law 10.639 / 03, arising in the midst of the politics of difference. The formative processes with teachers of basic education performatizam the subjects, (re) putting the subjective, the bodies, the cultural experiences in the school institutions.